Kardiochirurgia dorosłych New possibilities of endoscopic radial artery harvesting in surgical myocardial revascularisation procedures – a preliminary report - Urbanowicz, Tomasz; Misterski, Marcin; Perek, Bartłomiej; Buczkowski, Piotr; Jemielity, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: Radial artery is a commonly used graft in direct myocardial revascularisation procedure (CABG). A novel endoscopic harvesting technique may limit the surgical injury associated with the standard technique. Aim: The aim of the study was to present the endoscopic technique of radial artery harvesting in CABG procedures. Material and methods: Seven men at mean age of 57±4 years operated on in January and February 2006 were enrolled into the study. They underwent direct myocardial revascularisation on the beating heart (OPCAB). The radial artery was harvested with the use of Vasoview 6 Harvesting System (Guidant Corp., Indiannapolis, USA). Results: All radial arteries were successfully harvested without any macroscopic damage and then used as aorto-coronary bypass grafts. The length of the conduit ranged between 16 and 22 cm. As the experience improved, the mean total time of the procedure diminished from 70 minutes in the first case to 51 minutes in the last one. There were no surgical complications regarding the upper extremity. Conclusions: The endoscopic technique of radial artery harvesting is a useful and safe procedure that enables to obtain good aorto-coronary graft.